The Role of Beta-Endorphin in Cocaine-Induced Conditioned Place Preference, Its Extinction, and Reinstatement in Male and Female Mice - Singh, Prableen K.; Lutfy, Kabirullah (Frontiers in Behavioral Neuroscience, 2021)
Endogenous opioids have been implicated in cocaine reward. However, the role of each opioid peptide in this regard is unknown. Notably, the role of each peptide in extinction and reinstatement is not fully characterized. Thus, we assessed whether cocaine-induced conditioned place preference (CPP) and its extinction and reinstatement would be altered in the absence of beta-endorphin. We also examined if sex-related differences would exist in these processes. Male and female mice lacking beta-endorphin and their respective controls were tested for baseline place preference on day 1. On day 2, mice were treated with saline/cocaine (15 mg/kg) and confined to the vehicle- or drug-paired chamber for 30 min, respectively. In the afternoon, mice were treated with the alternate treatment and confined to the opposite chamber. Mice were then tested for CPP on day 3. Mice then received additional conditioning on this day as well as on day 4. Mice were then tested for CPP on day 5. Mice then received extinction training on day 9. On day 10, mice were tested for extinction and then reinstatement of CPP following a priming dose of cocaine (7.5 mg/kg). Male and female mice lacking beta-endorphin did not exhibit CPP following single conditioning with cocaine. On the other hand, only male mice lacking beta-endorphin failed to show CPP after repeated conditioning. Nonetheless, reinstatement of CPP was blunted in both male and female mice lacking beta-endorphin compared to controls. The present results suggest that beta-endorphin plays a functional role in cocaine-induced CPP and its reinstatement, and sex-related differences exist in the regulatory action of beta-endorphin on the acquisition but not reinstatement of cocaine CPP.